Morphological characterization of the nymphs rhipicephalus sanguineus ticks (Latreille, 1806) (Acari: Ixodidae). Description of the testes, integument, malpighian tubules, and midgut on the detachment day - de Oliveira, Patricia Rosa [UNESP]; Calligaris, Izabela Braggiao [UNESP]; Roma, Gislaine Cristina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
This study presents the morpho-histological and histochemical characterization of the testes, integument, Malpighian tubules, and midgut of engorged Rhipicephalus sanguineus nymphs on the detachment day, showing the morphological and physiological characteristics to this phase in the life cycle of these individuals. The testis is constituted by germinative cells (only spermatogonia) with large, round-shaped and strongly stained nuclei which are organized into cysts by a thin layer of somatic cells. The integument consists of a cuticle subdivided into epicuticle (lipoprotein) and procuticle (glycoproteic), and a layer of epithelial cells which present glycolipoprotein elements. The procuticle presents two distinct regions: the exocuticle (next to the epicuticle) and the endocuticle (next to the epithelial layer). The Malpighian tubules present a simple epithelium with small flat and/or cubic cells, which form its wall and delimitates a lumen full of lipoprotein material. The midgut consists of an epithelial wall formed by two types of digestive cells, spent cells and empty digest cells, and by generative cells supported by a basal lamina and a thin layer of muscular tissue. This study described the main organs of engorged nymphs of R. sanguineus, to generate information that can help researchers to better understand the biology of these ectoparasites; which is fundamental for the development of compounds that are less aggressive to the environment. In addition, if the immature stages of the ticks are controlled, the number of adult ticks able to cause damages to the animalsand to the man as wellis also under control. Microsc. Res. Tech. 75:727736, 2012. (C) 2011 Wiley Periodicals, Inc.
Keywords: Rhipicephalus sanguineus; Tick; Nymphs; Morphology; Histology